2013
DOI: 10.3182/20130904-3-fr-2041.00089
|View full text |Cite
|
Sign up to set email alerts
|

A new extension of the łrc; adaptive controller to drastically reduce the tracking time lags

Abstract: Abstract:The L 1 adaptive control scheme has proven its effectiveness and robustness in various fields thanks to its particular architecture where robustness and adaptation are decoupled. It was though noted that whenever the trajectory is varying, an inherent lag is present compared to other adaptive schemes due to the presence of a filter in the control architecture. To achieve a better tracking, we propose extending the architecture of the L 1 controller by augmenting it with a control input that could take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In order to eliminate the time lag [17,18] which appears using the classical L 1 adaptive control, we propose an augmented L 1 adaptive based on PI control which is illustrated in Fig. 2.…”
Section: Augmented L 1 Adaptive Control Based On a Pi Controlmentioning
confidence: 99%
“…In order to eliminate the time lag [17,18] which appears using the classical L 1 adaptive control, we propose an augmented L 1 adaptive based on PI control which is illustrated in Fig. 2.…”
Section: Augmented L 1 Adaptive Control Based On a Pi Controlmentioning
confidence: 99%
“…To deal with the issue of time lag, which appears when the controller is applied to track a time-varying reference trajectory, as in [18], an augmentation of the L 1 adaptive control is proposed. The augmented controller is illustrated in Fig.…”
Section: B Augmented L 1 Adaptive Controlmentioning
confidence: 99%
“…This drawback can be mitigated by augmenting the L1 adaptive control with a nonlinear proportional or a PI, PID controllers as proposed in [18], [19]. Among applications of the L1 adaptive control, one can cite the aerial vehicles, the underwater vehicles, the robot manipulators, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Augmenting the original L 1 controller with a proportional integral derivative controller improves the tracking performance without harming the robustness of the system. We have recently experimentally shown that a PI augmentation of the L 1 controller improves trajectory following by drastically decreasing the time lags [9]. The robustness towards a parameter variation was also validated through a scenario where the robot's buoyancy was modified.…”
Section: Introductionmentioning
confidence: 98%